The Effect of Operational Pressure, Distance Between Field Pipes, And Irrigation Level on The Growt, Yield, And Water Use Efficiency of Wheat (Triticum Aestivum L.) Under A T-Tape Drip Irrigation System - Ahmed Zaid Mahdi Alshuwaili; Ali Hamdhi Dheyab; Ahmed Zaid Mahdi Alshuwaili; Ali Hamdhi Dheyab (Jurnal MIPA dan Pembelajarannya, 2026)
This study aimed to evaluate the effect of operational pressure, spacing between field pipes, and irrigation level on plant growth parameters (plant height, dry matter of vegetative parts, grain yield, and water use efficiency) under a T-tape drip irrigation system in wheat crop (Triticum aestivum L.). A field experiment was conducted during the winter season of 2024–2025 in Safwan district, Basrah Governorate, Iraq. The experiment included three operational pressures (0.75, 1.00, and 1.25 m), three distances between field pipes (20, 30, and 40 cm), and two irrigation levels (100% and 80% of cumulative pan evaporation). The experiment was arranged according to a split-split plot design using RCBD with three replicates. Results showed that the 20 cm spacing recorded the highest values of plant height, dry matter of vegetative parts, grain yield, and water use efficiency compared with wider spacing. Increasing operating pressure significantly increased the above growth and production parameters. Irrigation at 100%Ep significantly increased the growth and production parameters compared with 80% Ep. Except for water use efficiency, the superiority was at 80% Ep compared with 100% Ep. Provides a